"INTER-LONGITUDE ASTRONOMY" (ILA) PROJECT: CURRENT HIGHLIGHTS AND PERSPECTIVES. I. MAGNETIC VS. NON-MAGNETIC INTERACTING BINARY STARS - Andronov, I. L.; Antoniuk, K. A.; Baklanov, A. V.; Breus, V. V.; Burwitz, V.; Chinarova, L. L.; Chochol, D.; Dubovsky, P. A.; Han, W.; Hegedus, T.; Henden, A.; Hric, L.; et al. (Одеські астрономічні публікації, 2010)
We present a review of highlights of our photometric and photo-polarimetric monitoring and mathematical modeling of interacting binary stars of different types classical, asynchronous, intermedi ate polars with 25 timescales corresponding to differ ent physical mechanisms and their combinations (part "Polar"); negative and positive superhumpers in nova-like and dwarf novae stars ("Superhumper"); symbiotic ("Symbiosis"); eclipsing variables with and without ev idence for a current mass transfer ("Eclipser") with a special emphasis on systems with a direct impact of the stream into the gainor star’s atmosphere, which we propose to call "Impactors", or V361 Lyr-type stars. Other parts of the ILA project are "Stellar Bell" (pul sating variables of different types and periods - M, SR, RV Tau, RR Lyr, Delta Sct) and "New Variable".